Muscle strength and joint range of motion of the spine and lower extremities in female prepubertal elite rhythmic and artistic gymnasts - Mandroukas, A.; Metaxas, I.; Michailidis, Y.; Metaxas, T. (Journal of Functional Morphology and Kinesiology, 2023)
The purpose of this study was to investigate and compare the passive joint range of motion (PROM) and muscle strength in prepubertal rhythmic gymnasts (RGs), artistic gymnasts (AGs), and a control group (CG) of the same age. A total of 54 prepubertal girls were divided into three groups: 18 RGs (age 11.14 ± 0.7, height 142.6 ± 5.81, and body mass 31.2 ± 3.63); 18 AGs (age 11.27 ± 0.99, height 139.6 ± 5.85, and body mass 31.7 ± 3.21), and 18 school girls who are defined as CG (age 10.55 ± 0.42, height 145.33 ± 6.95, and body mass 42.1 ± 8.21) participated in the study. All athletes were elites and participated in national competitions. The CG participated only in their school physical education program. Isokinetic peak torques were measured using an isokinetic dynamometer (Cybex II) at 60, 180, and 300°·sec-1. Body mass index was greater in the CG compared to RGs and AGs (p < 0.001). PROM in cervical extension in RG was significantly higher compared to the AG and CG (p < 0.001). The athlete groups, RG and AG, showed significantly greater PROM in knee flexion (p < 0.001), hip flexion (p < 0.001), and hip abduction (p < 0.05) compared to CG. PROM in hip flexion was different between the left and right leg in RGs. The relative muscle strength of the quadriceps in the RG and AG was significantly greater compared to CG (p < 0.001 and p < 0.01 respectively). Gymnastics training in prepubertal ages can improve neuromuscular function and increase the relative muscle strength. Therefore, it is essential to note that when evaluating children within the developmental ages, especially those involved in sports, the type of muscle strength to be assessed should be specified.